O teletrabalho e a responsabilidade civil do empregador quanto ao acidente, a saúde e a segurança - Serralvo, Letícia Lisboa Souza (2020)
This study is exploratory and aims to delineate the main aspects of the configuration of the employer's civil liability for work accidents and occupational diseases that occurred in the teleworking regime, in light of Law no. 13,467 / 17. The Legislator did not exhaust the subject, which raised several doubts regarding the axiological deficiency of Chapter II-A of articles 75-A to 75-E of the CLT, in particular regarding the standard of protection and prevention of diseases and work accidents. This study aims to elucidate the employer's civil liability for the health and safety of the teleworker. For this, the teleworking study demonstrating the factors that triggered its development, its peculiarities, and main characteristics, brought with its implementation. Based on these bases, the present work starts to build the premises for the application of civil liability in teleworking, analyzing the main accidents resulting from teleworking, disease prevention, tele-employer responsibilities, and news presented by labor reform and its implications. Thus, the research was conducted based on the principle basis in light of the Federal Constitution, the CLT, and ILO standards, as well as normative instructions on accidents, health, and safety at work. Finally, the conclusion is that the responsibility for teleworking will be subjective depending on the fault for its existence, and this will vary according to the compliance or not of the legal and contractual obligations assumed by the tele-employer